2018
DOI: 10.24105/ejbi.2018.14.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Prediction of Non-communicable Diseases to Improving Intervention Program in Bangladesh

Abstract: The prevention of non-communicable diseases (NCDs) has interested researchers in recent decades. According to the World Health Organization, NCD causes more deaths annually than all other causes combine, making it the leading cause of death globally [1]. A study [2] implementing an NCD prevention program using information communication technology was conducted by Kyushu University and Grameen Communications. A Portable Health Clinic (PHC) package with medical sensors (e.g., blood pressure [BP] monitors, blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…[23]. In this study, health status is assessed depending on the results of health checkup items provided by the PHC service [28]. We used the "Bangladesh-logic (B-logic)" risk stratification (which was created based on the international diagnostic standards) technique to rank the risk levels of each health checkup item result into four categories: healthy, caution, affected, and emergent [2,22,29].…”
Section: Health Statusmentioning
confidence: 99%
“…[23]. In this study, health status is assessed depending on the results of health checkup items provided by the PHC service [28]. We used the "Bangladesh-logic (B-logic)" risk stratification (which was created based on the international diagnostic standards) technique to rank the risk levels of each health checkup item result into four categories: healthy, caution, affected, and emergent [2,22,29].…”
Section: Health Statusmentioning
confidence: 99%
“…In many clinical studies, the gradient boosting machine-learning algorithm has been successfully used to predict cardiovascular diseases [13]. The gradient boosting decision tree method introduced by Friedman [68] predicted BMI with an accuracy of 0.91 [37]. In the current study, the boosted decision tree regression was found to be the best predictive model for uric acid, followed by decision forest regression.…”
Section: Principal Findingsmentioning
confidence: 62%
“…In many clinical studies, Gradient boosting machine learning algorithm has been successfully used to predict cardiovascular diseases [11]. The gradient boosting decision tree (GBDT) method by Friedman [33] predicted BMI with accuracy 0.91 [34]. In the current study boosted decision tree regression is found as the best predictive model followed by decision forest regression.…”
Section: Discussionmentioning
confidence: 77%